2004
DOI: 10.1021/jp049763p
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Study of Silica Gel by Positron Annihilation

Abstract: Microstructural studies of silica gel powder were carried out using positron annihilation lifetime spectroscopy (PALS) in conjunction with transmission electron microscopy (TEM). It is argued that the two distinct longlived components found (labeled by τ 3 and τ 4 ) may be ascribed to ortho positronium annihilation in microcavities within the grains and intergranular mesoscopic pores, respectively. In the latter type of void, a significant fraction decays via the three-photon mode. A simple physical picture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…This model calibration thus provides us with a methodology to gauge the minute pore structure in spongy silica gel material. 1 3.2. For Mesopores.…”
Section: For Microcavitiesmentioning
confidence: 99%
“…This model calibration thus provides us with a methodology to gauge the minute pore structure in spongy silica gel material. 1 3.2. For Mesopores.…”
Section: For Microcavitiesmentioning
confidence: 99%
“…It has been shown [16,17] that porous oxides may favor long o-Ps lifetimes and high intensity, and that silica gel is adequate media to study the formation and annihilation of positronium and an advanced material to investigate excited positronium states [18]. It has been observed that these systems present voids between the silica particles (interporosity) and that the particles themselves present nanoholes (intraporosity).…”
Section: Introductionmentioning
confidence: 99%
“…They also utilized N 2 adsorption to measure mesopore (>20 Å ) size of the same material. Dutta et al [32] utilized PALS to study microstructural properties of porous silica gel, identifying pores of $8 Å and a second mesoporous domain. PALS is …”
mentioning
confidence: 99%